All the world's a stage: evaluating psychiatry role-play based learning for medical students. (February 2015) - King, Joel; Hill, Kathryn; Gleason, Andrew
Objective: This paper describes an evaluation of an innovative approach, role-play based learning (RBL), as a vehicle for teaching psychiatry. The aim of this intervention, where medical students perform both doctor and patients roles, was to provide an interactive learning format that engaged students while developing clinical knowledge and communication skills in a structured, reflective environment. Method: Questionnaires were completed by 107 students from three clinical schools of the University of Melbourne. Data were analysed using descriptive and inferential statistics and thematic content analysis. Results: Student evaluations of the RBL sessions were overwhelmingly positive. Respondents reported improvements in engagement, confidence and empathy, as well as in their learning, and that the sessions provided good preparation for internship as well as for exams. Conclusion: The RBL tutorial programme is unique and flexible and could readily be adapted for use in other specialty rotations. It is also timely, given the increased interest in simulation prompted by increasing pressure on training places across the health sciences in Australia.